2018
DOI: 10.1039/c8nj04479a
|View full text |Cite
|
Sign up to set email alerts
|

Self-reversible mechanochromism and aggregation induced emission in neutral triarylmethanes and their application in water sensing

Abstract: Neutral triarylmethanes exhibit intramolecular exciplex formation, self-reversible mechanochromism, and aggregation induced/viscosity-dependent emission and sense water in organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…T.T Divya et al prepared three triarylmethane based compounds 20 a-c as 'turn off' fluorogenic probes for water sensor. [43] Compounds 20 a and 20 b exhibited a broad emission peak with positive solvatochromism. The weak emission peak was observed at 350 nm for 20 a, whereas broad red-shift emission at 380 nm and 390 nm observed for 20 b due to exciplex formation.…”
Section: Probes Based On Solvatochromismmentioning
confidence: 99%
See 1 more Smart Citation
“…T.T Divya et al prepared three triarylmethane based compounds 20 a-c as 'turn off' fluorogenic probes for water sensor. [43] Compounds 20 a and 20 b exhibited a broad emission peak with positive solvatochromism. The weak emission peak was observed at 350 nm for 20 a, whereas broad red-shift emission at 380 nm and 390 nm observed for 20 b due to exciplex formation.…”
Section: Probes Based On Solvatochromismmentioning
confidence: 99%
“…T.T Divya et al. prepared three triarylmethane based compounds 20 a – c as ′turn off′ fluorogenic probes for water sensor [43] . Compounds 20 a and 20 b exhibited a broad emission peak with positive solvatochromism.…”
Section: Probes Based On Solvatochromismmentioning
confidence: 99%
“…Thus, the analyses further validate the AIE-induced fluorescence enhancement by the RIR mechanism. 47,48 Interestingly, in Figure S14, SI, it can be observed that with the increasing concentration of NAP-1 at room temperature from 0.1 to 100 μM, the intensity of the keto emission band is increased with a gradual decrease of the enol emission band. This speculates that in the excited state a facile proton transfer process takes place with the increasing concentration or aggregation of the compound, thereby facilitating the AIEinduced emission through RIR.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Divya et al designed and synthesized a mechanoresponsive fluorophore, 73 (Chart 8), having perylene and 4,4 0 -methylene bis(N,N 0 -dimethylaniline) units and studied its mechanochromic properties. 137 The molecule 73 showed orange red emission at 610 nm in the pristine form and a hypsochromic shift of 74 nm upon grinding was observed and the ground powder showed emission at 536 nm with yellow fluorescence (Fig. 40a and b).…”
Section: Miscellaneous Compoundsmentioning
confidence: 98%